Nucleolar and Coiled-Body Phosphoprotein 1 Is Associated With Stemness and Represents a Potential Therapeutic Target in Triple-Negative Breast Cancer - Chen, Sisi; Li, Ying; Wu, Muyao; Xue, Lian; Zhu, Jianyu; Wu, Mi; Zhang, Qiuting; He, Guangchun; Li, Guifei; Fu, Shujun; Zheng, Chanjuan; Deng, Xiyun (Frontiers in Oncology, 2022)
Triple-negative breast cancer (TNBC) is the most aggressive subtype of breast cancer and lacks approved specific targeted therapies. One of major reasons why TNBC is difficult to treat is the high proportion of cancer stem cells within the tumor tissue. Nucleolus is the location of ribosome biogenesis which is frequently overactivated in cancer cells. Overactivation of ribosome biogenesis easily drives malignant transformation of cancer. Nucleolar and coiled-body phosphoprotein 1 (NOLC1) is a nucleolar protein responsible for nucleolus organization and rRNA synthesis and plays an important role in ribosome biogenesis. However, the correlation of NOLC1 expression with patient prognosis and its value as a therapeutic target have not been evaluated in TNBC. In the current study, we found that the expression of NOLC1 was higher in breast cancer tissues than normal tissues and NOLC1 was expressed at a higher level in TNBC than other subtypes of breast cancer. GSEA analysis showed that stemness-related pathways were significantly enriched in breast cancer with high NOLC1 expression. Further analyses using gene expression profiling interactive analysis 2 (GEPIA2), tumor immune estimation resource (TIMER) and search tool for retrieval of interacting genes/proteins (STRING) databases showed that NOLC1 was significantly associated with stemness in both all breast cancer and basal-like breast cancer/TNBC patients. Knockdown of NOLC1 by siRNA decreased the protein level of the key stemness regulator c-Myc in TNBC cell line MDA-MB-231. Univariate and multivariate Cox regression analysis demonstrated that NOLC1 was an independent risk factor in breast cancer. Survival analysis performed in the PrognoScan and Kaplan-Meier plotter databases revealed that high expression of NOLC1 was associated with poor prognosis in both all breast cancer and TNBC patients. These findings suggest that NOLC1 is closely associated with the stemness properties of TNBC and represents a potential therapeutic target for TNBC.